ANALISIS YURIDIS KEBEBASAN BERSERIKAT PEGAWAI NEGERI SIPIL DALAM PARTAI POLITIK - Made Dian Supraptini; I Gusti Ayu Puspawati (Kertha Negara : Journal Ilmu Hukum, 2014)
The regulation regarding freedom of association as a right of every Indonesian citizens as stipulated within the Constitution of Republic Indonesia in 1945. Due to that, a problem had arisen regarding restriction of civil servant (here in after shall be abbreviated as “PNS”) who are Indonesian citizens to have freedom of association in political parties, meanwhile Indonesia had guaranteed its citizens freedom of association. Method that used in this research is the normative research method. Freedom of association existed as a right of Indonesian citizens remarks civil servant has the right to do it because civil servant are also Indonesian citizens, however there is the restriction of civil servant became member or official of political parties. The restriction as stipulated in Article 3 paragraph (3) Act No. 43 Year 1999 and further regulated through Article 2 paragraph (1) Government Regulation No. 37 Year 2004.